Self-cleavage-dependent and -independent functions of Adgrg1/Gpr56 in mice - Frank E. Kwarcinski; Tyler F. Bernadyn; James P. Teuber; Mariane Nascimento; Ingrid Bergin; Tingzhen Shen; Riya Gandhi; Xinyi Lu; Matthew J. Brody; Michael Holinstat; Gregory G. Tall (Proceedings of the National Academy of Sciences, 2026)
Adhesion G protein–coupled receptors (AGPCRs) regulate essential physiological processes through interactions between their ectodomains and adjacent cell surface proteins or extracellular matrix components (ECM). AGPCRs distinctively arrive at the plasma membrane as self-cleaved holoreceptors with noncovalently associated N-terminal (NTF) and C-terminal fragments (CTF). Canonical AGPCR signaling proceeds in three sequential steps; NTF adhesive domains bind to ligands, extracellular shear force mediates NTF and CTF dissociation, a tethered peptide agonist (TA) is exposed and binds to the CTF orthosteric site to stabilize the active state receptor. Depending on the cellular context, both autoproteolysis-deficient and perhaps, a few cleavage-capable AGPCRs may be activated without NTF dissociation or the action of the TA. To discriminate the functional consequences of these signaling modes in vivo, we created a cleavage-deficient, Gpr56 H381S knock-in mouse and investigated five distinct defective phenotypes of Gpr56 knockout mice. One prominent phenotype, brain malformation that parallels human bilateral frontoparietal polymicrogyria (BFPP) disease, is characterized by dysplasia of the cortex and cerebellum and neuron heterotopia. Brain histology analyses confirmed that Gpr56 H381S mice had comparable cerebellar structural irregularities as Gpr56 knockout mice, indicating that TA agonism is indispensable for proper cerebellar lobule formation and neuronal migration. TA-dependent signaling was also required for male mouse fertility, but not for adult cardiomyocyte homeostatic functions, platelet-dependent hemostasis, or axon myelination in the central nervous system. These findings indicate that GPR56 has multiple modes of activation and that these signaling outcomes are likely driven by NTF interactions with specific ligands including collagen and transglutaminase-2.